Diurnal variation of transitory starch metabolism is regulated by plastid proteins WXR1/WXR3 in Arabidopsis young seedlings. (11th February 2021) - Zou, Wenjiao; Liu, Kui; Gao, Xueping; Yu, Changjiang; Wang, Xiaofei; Shi, Junjie; Chao, Yanru; Yu, Qian; Zhou, Gongke; Ge, Lei
Abstract: Transitory starch is the portion of starch that is synthesized during the day in the chloroplast and usually used for plant growth overnight. Here, we report altered metabolism of transitory starch in the wxr1 / wxr3 ( weak auxin response 1/3 ) mutants of Arabidopsis. WXR1/WXR3 were previously reported to regulate root growth of young seedlings and affect the auxin response mediated by auxin polar transport in Arabidopsis. In this study the wxr1 / wxr3 mutants accumulated transitory starch in cotyledon, young leaf, and hypocotyl at the end of night. WXR1/WXR3 expression showed diurnal variation. Grafting experiments indicated that the WXRs in root were necessary for proper starch metabolism and plant growth. We also found that photosynthesis was inhibited and the transcription level of DIN1/DIN6 ( Dark-Inducible 1/6 ) was reduced in wxr1/wxr3 . The mutants also showed a defect in the ionic equilibrium of Na + and K +, consistent with our bioinformatics data that genes related to ionic equilibrium were misregulated in wxr1 . Loss of function of WXR1 also resulted in abnormal trafficking of membrane lipids and proteins. This study reveals that the plastid proteins WXR1/WXR3 play important roles in promoting transitory starch degradation for plant growth over night, possibly through regulating ionic equilibrium in the root. Abstract : Plastid proteins WXR1/WXR3 in root are involved in K + assimilation, in association with changes in the utilization of transitory starch in chloroplast and intracellular membrane trafficking.